Can gender come to the rescue of foreign policy? : an exploration into the ways in which the (mis)understanding of gender influences the making of foreign policy - Meyer, Christa (Stellenbosch : Stellenbosch University, 2012)
Thesis (MA)--Stellenbosch University, 2002.